House K in Senjak - Pantović, Ksenija; Kavran, Jasna (Arhitektura i urbanizam, 2023)
The paper will consider the design and conceptual decisions related to the design of Villa K in Senjak. The initial task was to design a single-family villa with all of the accompanying contents. The villa acquired specific features in relation to the project task, and is a contemporary interpretation of the various postulates of the modernist heritage, with a free plan, a roof terrace and a dominant spatial continuity between the interior and the exterior. Also considered here will be its dynamic, diverse and historical context. Special attention will be focused on the specific relationship between the exterior and interior, i.e. the simultaneous development of a concept involving an introverted approach to the street and an extroverted approach to the yard, that is, the south side. In this sense, particular attention will be given to the urban concept, but also to the functional organization and arrangement of the contents, architectural form and composition, as well as aspects of energy efficiency and construction. Subtle interventions on the villa’s volumes and wall surfaces will also be analyzed, as well as specific perceptual transformations and ways of perceiving the architecture. In addition, the paper will give special attention to interventions in the interior, which are an inseparable part of the architectural concept. Thus, the interior arrangement is guided by the idea of providing maximum comfort to the users, followed by the design of certain elements in the space. Each of these aspects will clarify more deeply the main conceptual determinants, the positioning of the building on the plot, and the use of greenery in the exterior and interior, as well as other questions from the project determining the shape of the villa.
Keywords: extroversion; introversion; concept; context; energy efficiency